Investigation of CNC Milling Machining Parameters on Surface Roughness - Alyas, Rasha Ramiz (Al-Khwarizmi Engineering Journal, 2018)
Milling Machining is a widely accepted nontraditional machining technique used to produce parts with complex shapes and configurations. The material is removed in two stages roughing and finishing, the flat end cutter removed the unwanted part of material, then finished by end mill cutter. In milling technique, the role of machining factors such as cutting depth, spindle speed and feed has been studied using Taguchi technique to find its effectiveness on surface roughness.  Practical procedure is done by Taguchi Standard matrix. CNC milling is the most conventional process which is used for removing of material from workpiece to perform the needed shapes. The results and relations indicate that the rate of feed is very important factor for modeling surface roughness. The plot of S/N ratio shows that the optimum combination of the milling factors that gives the best value of surface accuracy. The best combination of milling factors has also been predicted to minimize the surface roughness.